Antihypertensive agents safety during pregnancy - E V Karpova; A A Orazmuradov; I A Litvinenko; U A Andreeva; E N Kryukova; T V Bratchikova; V A Lusov (RUDN Journal of Medicine, 2011)
The article discusses pregnancy course and labor outcomes in women with chronic hypertension. We divided all pregnant into two groups in dependence on the kind of antihypertensive treatment. The main group treatment was nebivalol monotherapy, the control group took combined medications in different compositions (atenolol, methyldopa, nifedipin). We revealed nebivalol therapy significantly decreased the number of gestational complications and adverse perinatal outcomes and in pregnant with chronic hypertension.